Ecdótica e edição pessoana - Giménez, Diego (Pessoa Plural, 2020)
DUARTE, Luiz Fagundes (2018). Do Caos Redivivo, Ensaios de Crítica Textual sobre Fernando Pessoa. Lisboa: Imprensa Nacional-Casa da Moeda, 222 pp. Colecção Pessoana. ISBN: 978- 972-27-2656-6